Engaging Science Learners at Disadvantaged schools in South Africa in the Use of Culturally-Anchored Virtual Reality Simulations for Inquiry-based Learning - Ramnarain, Umesh; Penn, Mafor; Mdlalose, Noluthando (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
This study explores the perceptions and experiences of high school learners at historically disadvantaged schools in South Africa who engaged with Culturally-Anchored Virtual Reality Simulations (CAVARS) for science learning. Using a qualitative case study approach, data were collected through group interviews following a classroom-based intervention. Thematic analysis revealed key themes: emotional engagement, enhanced conceptual understanding, preference for experiential learning, cultural relevance, and the desire for equitable access to educational technology. Implications are discussed in terms of pedagogical practice and the integration of immersive technologies in resource-constrained educational contexts.